Investigation of the bainitic reaction in a CuAlNiMnFe shape memory alloy - Benke M.; Mertinger V.; Pekker P. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Despite their favorable properties, brittle nature of the CuAlNi shape memory alloys limits their suitability. To increase their ductility, Mn and Fe were added to the base CuAlNi alloy. To reveal the applicability of the developed CuAlNiMn and CuAlNiMnFe alloys as functional materials, the effect of ageing on the thermoelastic martensitic transformation was investigated. During the first heating of the aged samples the thermoelastic γ’ → β transformation occurred, which was followed by a bainitic transformation. This transformation inhibited the further thermoelastic martensitic transformations. The present paper covers heat flux DSC, SEM, and TEM investigations of the bainitic transformation. A feasible mechanism of the bainitic transformation in these alloys is suggested based on the results of the examinations.